Technical and economic advantages of using elongating mandrel made of forged blank when rolling on a continuous mill with a controlled‑movable mandrel - A. I. Tovsteleva (Литьë и металлургия)
In the article, the current problem of reducing the cost of pipe‑rolling products, which is especially acute in the world market of metal products high competition conditions is considered. A significant share in the cost of pipe products stands at the cost of rolling tools. Reducing the cost of buying a deforming tool allows you to make considerable savings in the seamless pipes’ production. The article presents: analysis of the economic efficiency of manufacturing long cylindrical mandrels from a semi‑finished product – forged billet at OJSC «BSW – management company of «BMC» holding»; development of the technological process for the production of long mandrels depending on the required size; the results on the manufacture of long cylindrical mandrels from forged billet at OJSC «BSW – management company of «BMC» holding», as well as their industrial tests in the conditions of the pipe rolling shop. A positive result of using long mandrels of the PQF mill made of forged blanks was obtained.